Smart Technologies (ST) application in identifying mould growth defects in defect management works for operated heritage buildings in Penang, Malaysia: a pilot survey / Ahmad Mu'az Ahmad, Nur Azfahani Ahmad and Mohd Azian Zaidi - Ahmad, Ahmad Mu'az; Ahmad, Nur Azfahani; Zaidi, Mohd Azian (2022)
In Malaysia, there are many heritage buildings that are still in operation and are heavily affected by mould growth defects due to high moisture content, poor air circulation, and other factors that lead to the degradation and dilapidation of these buildings. Through government bodies and related agencies, defects in heritage buildings are still maintained with certain procedures which consist of generic documentation. However, these procedures are still operated in a conventional way and lacking with smart technologies application that will be able to identify the related defect in a more precise and high-tech approach for these heritage buildings. In conjunction with the Fourth Industrial Revolution (IR 4.0) and Sustainable Development Goals (SDG), it is significant to improvise current defect management works with Smart Technology (ST) applications. Therefore, this research focuses on exploring the significant ST applications that can identify the mould growth defects inside heritage buildings in a more precise approach. Through preliminary study, it will focus on heritage buildings with mould growth issues in Penang to formulate a significant defect management work that can be integrated with ST applications. This paper will present the results from a preliminary survey conducted with experts who have suggested suitable ST applications to identify mould growth defects in a selected case study in Penang. The pilot survey shows that virtual reality (VR) is the best Smart technologies that can be integrated with defect management works in order to identify mould growth issues. The research will provide relevant insights from this panel of experts through a purposive sampling approach to help the government or local council to establish a more sustainable heritage building.